1986
DOI: 10.3109/03009738609178488
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Skeletal Malformations in the Offspring of Rats Fed a Zinc Deficient Diet

Abstract: Pregnant rats were subjected t o a t r a c e metal poor diet (1.2 ppm zinc, 5.9 ppm copper, 40 ppm manganese) during t h e entire gestation. The r a t mothers did not gain weight during pregnancy and showed decreased liver weight and lowered serum glucose levels on gestational day 20. The offspring exhibited decreased body and placental weights, delayed ossification of t h e skeleton, and a n increased resorption rate. We also found 4 % skeletal malformations in the offspring (0 % in t h e controls), which clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The role of zinc in the skeleton, which contains the major portion of total body zinc, is not clear [30]. However, resulting skeletal malformation in the offspring whose dams were fed a Zn-restricted diet during pregnancy is well known [31,32]. Skeletal growth impairment is a common finding associated with zinc deficiency [33].…”
Section: Discussionmentioning
confidence: 99%
“…The role of zinc in the skeleton, which contains the major portion of total body zinc, is not clear [30]. However, resulting skeletal malformation in the offspring whose dams were fed a Zn-restricted diet during pregnancy is well known [31,32]. Skeletal growth impairment is a common finding associated with zinc deficiency [33].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that normal pregnant U rats on a zinc-deficient diet are more prone to have fetal skeletal malformations than H rats given the same diet (54). A leakage of albumin via the kidneys may predispose for trace metal shortage, because albumin serves as carrier and plasma reservoir for several of these, including zinc.…”
Section: Ud Hn Hdmentioning
confidence: 99%
“…The last week of gestation is considered to be a ''catabolic phase'' in which maternal nutritional stores are consumed to support the rapidly growing fetus. Deficiencies of specific nutrients, such as zinc, also can lead to delayed ossification (Styrud et al, 1986).…”
Section: Determinants Of Ossification Ratementioning
confidence: 99%